1983
DOI: 10.1042/bj2110227
|View full text |Cite
|
Sign up to set email alerts
|

Equilibria amongst different molybdenum (V)-containing species from sulphite oxidase. Evidence for a halide ligand of molybdenum in the low-pH species

Abstract: The interaction of chloride, fluoride and phosphate ions with the molybdenum centre of sulphite oxidase in the pH range 6.2 to 9.6 has been studied by e.p.r. of Mo(V) in the enzyme reduced by sulphite. Detailed studies were made from e.p.r. spectra recorded at about 120K and more limited studies from spectra of liquid samples at about 295K and also from enzyme activity measurements. Interconversion between low-pH and high-pH Mo(V) e.p.r. signal-giving species [described by Lamy, Gutteridge & Bray (1980) Bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
122
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(134 citation statements)
references
References 18 publications
10
122
2
Order By: Relevance
“…Previous work has shown that the addition of chloride promotes the conversion of the high-pH species to the low-pH species. 13 Moreover, Bray and co-workers found that increasing the chloride concentration by a factor of 10 shifted the pK a of the interconversion between high-and low-pH signal-giving species by one pH unit. 13 In addition, they reported that the low-pH EPR signals were identical in the absence and presence of chloride and attributed this to trace amounts of contaminating chloride in their "chloride-free" buffers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work has shown that the addition of chloride promotes the conversion of the high-pH species to the low-pH species. 13 Moreover, Bray and co-workers found that increasing the chloride concentration by a factor of 10 shifted the pK a of the interconversion between high-and low-pH signal-giving species by one pH unit. 13 In addition, they reported that the low-pH EPR signals were identical in the absence and presence of chloride and attributed this to trace amounts of contaminating chloride in their "chloride-free" buffers.…”
Section: Resultsmentioning
confidence: 99%
“…13 Moreover, Bray and co-workers found that increasing the chloride concentration by a factor of 10 shifted the pK a of the interconversion between high-and low-pH signal-giving species by one pH unit. 13 In addition, they reported that the low-pH EPR signals were identical in the absence and presence of chloride and attributed this to trace amounts of contaminating chloride in their "chloride-free" buffers. 25 Figure 1b and c compare the low-pH spectra obtained in the presence and in the rigorous absence of added chloride.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…a SAD, b NITRATE, c PERCHLORATE, and d CYANIDE, The2mFo-DFc electron density maps contoured at 1r (blue) and the mFo-DFc electron density maps contoured at 3r (red) calculated in the absence of a sixth ligand (left) and calculated in the presence of the sulfur atom in the final refinement (right) g n * 0.5 for 35,37 Cl and I = 1/2, g n = 2.26 for 31 P) and hence superhyperfine structure from these nuclei might be observed in the EPR spectra associated with Mo(V) species. Hyperfine couplings associated with chloride nuclei in equatorial positions have been reported in model complexes of Mo(V) ions in nearly octahedral or squarepyramidal coordination [24] and in the molybdenum enzyme sulfite oxidase [25]. Larger couplings should be expected for the phosphorous atom because of the higher nuclear g factor (g n = 2.26).…”
Section: Analysis Of the Structures Around The Molybdenum Active Sitementioning
confidence: 99%
“…The high-pH signal occurs at low anion concentrations and at high-pH values, while the low-pH/Cl -signal occurs at low pH and high chloride. 37,38 A third category of signals are those from oxy-anion complexes, which tend to form at low pH and high oxy-anion concentrations. SO Mo V EPR signals arising from anion accessed by following the link in the citation at the bottom of the page.…”
mentioning
confidence: 99%